The effect of denervation upon the functional properties of myosin and its fragments - Kalamkarova, M B; Moskalenko, I E; Podlubnaya, Z A; Strankfeld, I G (Physiologia Bohemoslovaca, 1976)
A study has been made of some structural and enzymatic properties of myosin and its fragments from denervated white muscles of rabbit in the course of atrophy using different methods: UV-luminiscence, flow birefringence, electromicroscopy, viscosimetry and enzymatic measurements. All the studied parameters had a tendency to decrease; at prolonged observation some properties were partially restored. Considerable changes of structural properties of LMM were revealed: the ability of LMM from denervated muscle to form high-ordered structures which is characteristic of LMM from normal muscle decreased considerably.
Keywords: Birefringence; luminiscenční měření; denervace svalu; adenosintrifosfatasy; viskozita; spektrální analýza; Cholinesterases; Spectrum Analysis; Myosins; dvojitý lom; Muscle Denervation; králíci; elektronová mikroskopie; Time Factors; Animals; Viscosity; konformace proteinů; zvířata; Adenosine Triphosphatases; Microscopy, Electron; časové faktory; Rabbits; cholinesterasy; Protein Conformation; myosiny; Luminescent Measurements